S3 guideline “Smoking and Tobacco Dependence: Screening, Diagnosis, and Treatment” - short version: guidelines - Batra, Anil; Kiefer, Falk; Andreas, Stefan; Gohlke, Helmut; Klein, Marianne; Kotz, Daniel; Mons, Ute; Mühlig, Stephan; Pötschke-Langer, Martina; Preuss, Ulrich W.; Rüther, Tobias; Rustler, Christa; et al. (European addiction research, 2022)
Introduction: In addition to the prevention of tobacco consumption, the establishment and assurance of high-quality treatment for harmful use and dependence on tobacco products remains an important health-related task in Germany. Regular updating of the Association of the Scientific Medical Societies (AWMF) S3 guideline “Smoking and Tobacco Dependence: Screening, Diagnosis, and Treatment” (Tobacco Guideline) offers a sustainable and reputable source of knowledge on smoking cessation. Methods: Under the auspices of the German Society for Psychiatry, Psychotherapy, Psychosomatics, and Neurology (DGPPN) and the German Society for Addiction Research and Addiction Therapy (DG-Sucht), the Tobacco Guideline was revised in 2019-2020 by 63 experts, who were involved in the development process of the text, in 11 working groups. Undue influence of conflicts of interest on the guideline could be minimized through careful conflict of interest management. Delegates from 50 professional societies discussed the 80 guideline recommendations and voted online. Results: In addition to recommendations for screening and diagnostics, the Tobacco Guideline takes a positive stance towards the use of low-threshold counseling and support services. If, due to the severity of the tobacco-related disorder, brief counseling, telephone counseling, or internet- or smartphone-based methods are not sufficiently effective, individual or group behavioral therapy, possibly in combination with medication, is indicated. If nicotine replacement therapy is not effective, varenicline or bupropion should be offered. Alternative strategies with a lower level of recommendation are hypnotherapy, mindfulness-based treatments, or medication with cytisine. In adolescents and pregnant women, the use of medication should be limited to well-specified exceptions and nicotine replacement. The mean agreement with the recommendations reached a value of 98%. A general overview of the treatment recommendations of the Tobacco Guideline is provided by three clinical algorithms.